A New Naqli Aqli Indexing Content (Naqli-IC) Psycho-spiritual Neurofeedback (NFB)Training for Recovering Addicts (International Journal of Scientific Research and Management (IJSRM), 2017)
The current nature of drug treatment and rehabilitation models lacks intervention that relates to the physiology and spirituality of the individual. Islamic reveal knowledge based on al-Quran, hadith, tafseer, zikhir,doa’, Mathourat and roqiyyah, and other Islamic references are very rich resources which need to be discovered and used as guidance in solving problems from all aspects of life, including problem in drug addictions. The integration of Islamic knowledge inputs with new technology will synergize the strength of both the naqli and aqli aspects of both worlds. The aim of this study is to propose a new Islamic (naqli aqli) indexing content to be used in neuro feedback training for recovering addicts. The objectives of this study are (1) to investigate the existing model of indexing content in Islamic knowledge therapy in drug addiction.(2) to analyse existing index content of Islamic knowledge therapy for drug addiction.(3) to develop a new Naqli indexing content for psycho-spiritual neurofeedback training for recovering addicts. The textual and content analysis and textual evaluation will be used as methodology for this study. Alquraan, hadith, tafseer, Arabic manuscripts and on line references will be used in developing the Naqli indexing content. It is expected that the finding from this study,a new naqli indexing content will be made available. This new naqli content, than will be developed into audiovisual by the other group to be used as new stimulants in the neuro feedback training system. This is very significant effort in proving scientifically, the strength of Islamic reveal knowledge in drug addiction treatment